Educational enigma for future talent: roles of teachers as catalysts in inspiring high school students to pursue higher education - Sharifah Rahama Amirul; Sharifah Milda Amirul; Rasid Mail; Datu Razali Datu Eranza; Jurry Foo Michael; Colonius Atang (Journal of Education and Learning (EduLearn), 2026)
Numerous studies have been conducted from the perspective of high school students, examining the factors that contribute to their refusal to pursue higher education institutions (HEIs). Presently, there is limited study investigating teachers’ viewpoints regarding their roles as change agents in encouraging students towards HEIs. Therefore, this study seeks to provide new insights from educators that can strengthen teacher training and development, as well as inform the creation of customised intervention strategies designed to promote a culture of academic aspiration and achievement among students. Grounded in the philosophical premise of social constructivism, the study employed a qualitative methodology, analysing a sample of ten teachers selected by purposive sampling. In-depth interviews were conducted, and the data were analysed using thematic analysis. Our findings provide a comprehensive understanding of the strategies teachers used and the challenges they faced when motivating students to pursue HEIs. We proposed a conceptual study framework built from these findings, illustrating the interaction between teachers’ duties, educational problems, and students’ aspirations for further education. Our research is significant as it advances theory development in educational psychology and motivation theory by revealing new themes and relationships that can enhance existing theoretical frameworks.